Adherence to Therapeutic Footwear in Type 2 Diabetes in Malta - Formosa, Cynthia; Borg, Anthea; Papanas, Nikolaos; Mizzi, Stephen (Experimental and Clinical Endocrinology & Diabetes, 2020)
Background The literature reports that people living with diabetes do not adhere to their prescribed therapeutic footwear as instructed. The reason for this is still uncertian although certain footwear characteristics seem to reasons reported leading to reduced level of adherence.Objectives To explore the reasons for current adherence or otherwise to prescribed stock footwear amongst patients living with type-2 diabetes.Methods An exploratory qualitative design method using an Interpretative Phenomenological Analysis [IPA] was employed in this research. Employing purposive sampling, twelve participants were recruited and interviewed. Interviews were recorded, transcribed and later analysed.Results Common themes that emerged from this study fell under 2 main categories including ‘Adherence’ and ‘Non – Adherence’ to wearing the prescribed stock footwear. A number of themes were identified with regards to the reasons for such adherence or otherwise by respective participants including footwear characteristics, service provision, peer pressure and the patient’s knowledge and attitudes.Conclusion This study demonstrated suboptimal adherence to wearing therapeutic footwear among people with type 2 diabetes. Although the literature highlights the importance of adherence to therapeutic footwear in high risk populations for the prevention of diabetic foot complications, this study provides the reasons as to why patients still do not comply in wearing their prescribed therapeutic footwear. In order to improve behavioral changes patients would require on-going care, empowerment and support combined with educational programs to achieve a higher level of adherence. More research is warranted to explore further psychosocial interventions in diabetes care.
Keywords: adherence; behaviour; diabetes; diabetic foot; therapeutic footwear